Evaluation of an Integrated Rescue Task Force Model for Active Threat Response. (4th May 2019) - Bachman, Michael W.; Anzalone, Brendan C.; Williams, Jefferson G.; DeLuca, Mallory B.; Garner, Donald G.; Preddy, James E.; Cabanas, Jose G.; Myers, J. Brent
Abstract: Objective : An integrated response to active threat events is essential to saving lives. Coordination of law enforcement officer (LEO) and emergency medical services (EMS) roles requires joint training, as maximizing survival is a shared responsibility. We sought to evaluate the performance of an integrated LEO-EMS Rescue Task Force (RTF) response to a simulated active shooter incident utilizing objective performance measures.Methods: Following prior didactic training, we conducted a series of evaluation scenarios for EMS providers and patrol officers in our urban/suburban advanced life support EMS system (pop. 1, 000, 000). The scenario-tested command staff, LEOs tasked with neutralizing an active shooter threat, and two RTFs of LEOs and EMS providers each tasked with triage and treatment of 11 simulated casualties scattered over 2 office building floors totaling 13, 000 square feet. Trained evaluators recorded performance on 30 objective data elements related to LEO-EMS operations/communication, time intervals, and trauma care. Data were analyzed using descriptive statistics and t-tests for between group comparisons.Results: Over 18 days, 69 scenario events evaluated 388 EMS providers and 468 LEOs. Overall median (90th percentile) times in minutes from dispatch were: unified command established 4.1 (5.5), RTF assembled 9.4 (13.5), first victim contact 11.9 (16.5), first victim to internal casualty collection point (CCP) 16.6 (20.8), all victims ready for evacuation 21.6 (26.0). Life-saving interventions included tourniquet placed: 96% (95% CI 92–99) and LEO placed tourniquet: 88% (79–94). Clinical delays included inappropriate chest decompression: 4% (2–9) and unnecessary initial treatment: 17% (12–25). Correct operational actions included communication with LEO to ensure EMS was safe to treat: 70% (61-77) and appropriate CCP selection: 84% (74–91). Incorrect operational actions included failure to maintain protective LEO-EMS formation: 49% (45–62) and inappropriate single patient evacuation: 20% (14–28). Limitations included the lack of a pre-training control group for this novel program.Conclusions: We described the performance of an integrated LEO-EMS Rescue Task Force response to a simulated active shooter event in a large city. In general, clinical care was appropriate while operational targets can be improved. Objective measurement of response goals may be used for benchmarking and performance improvement for active threat events.